ВЛИЯНИЕ КОМПЛЕКСНОЙ ТЕРАПИИ С ПРИМЕНЕНИЕМ СУЛОДЕКСИДА НА ПОКАЗАТЕЛИ АРТЕРИАЛЬНОГО ДАВЛЕНИЯ У БОЛЬНЫХ ПСОРИАЗОМ - Тошев, Сухроб Уктамжон угли; Абдуллаев , Хасан Давлатович; Маматов, Жахонгир Мавлонович (Educational Research in Universal Sciences, 2024)
This article examines the effect of complex therapy, including sulodexide, on blood pressure in patients suffering from psoriasis. Psoriasis, as a chronic inflammatory disease, may be accompanied by changes in the circulatory system, including blood pressure. Sulodexide, which is a group of drugs known for their anticoagulant and anti-inflammatory properties, is considered as a potential component of complex therapy for psoriasis. The article presents an analysis of the effectiveness of sulodexide in the context of normalizing blood pressure in patients with psoriasis. The results obtained allow us to evaluate the possibility of integrating sulodexide into the complex treatment of psoriasis in order to improve not only skin symptoms, but also the general condition of patients, highlighting the potential of this drug in managing concomitant cardiovascular aspects in this dermatological disease.